Implementasi Pencegahan dan Penangulangan Covid 19 ‎dalam Rangka Peningkatan Ketahanan Pangan Masyarakat ‎Ngagel Baru Surabaya ‎ - Fauzie Senoaji; Novita, Dina (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2023)
The purpose of this study was to assess food security in the Ngagel Baru sub-district, Surabaya in the era of the Covid-19 pandemic, because the problem of food security was apparently not only stopped at the problem of distribution but rather how food security could be met properly due to the decline in income of some people. due to termination of employment or loss of income because there are no consumers who buy or use the services of producers. This study also aims to find out how to overcome food security through various community service activities, because food is a basic need of every human being. The results of this study indicate that the lock down activity significantly affects the income level of the Ngagel Baru village community which can threaten food security in the current pandemic era. In this community service activity, the community feels helped through the knowledge and skills they have acquired so that they can increase their economic capacity either individually or in community groups in order to increase food security to become a prosperous society.